A model of a personalized educational program of advanced training courses for teaching staff: andragogical approach - O. V. Berezhnaya; A. L. Kobleva (Вестник Северо-Кавказского федерального университета)
Introduction. The article examines organizational and methodological issues of the system of advanced training for teaching staff based on the individual characteristics and professional experience of adult learners. The authors focus on the importance of introducing personalized practices of advanced training of teachers and organizing relevant educational needs of teachers and the teaching labor market. As a tool for solving this problem, it is proposed to develop and implement personalized educational programs in the organization of advanced training courses for teachers. Goal. The study aims to develop a model for designing personalized educational programs of advanced training courses taking into account andragogical principles. Materials and methods. The work used the methods of content analysis of literature, regulatory documents related to the topic of research and design.Results and discussion. As a result of the content analysis of scientific and methodological literature on the topic of the research and materials of the Concept of Development of Teaching Staff, the most common factors causing complexity in organizing the process of advanced training of teachers and its results were determined. Based on the data obtained, conclusions were made about the need to strengthen the teacher-centered policy in the organization and personalized support of the teacher training process. The model for designing personalized educational programs of advanced training courses developed on the principles of the andragogical approach to adult education confirms the practical significance of the study. The model is presented as a figure in order to clearly demonstrate how andragogical principles are taken into account at all stages of designing a personalized program of advanced training courses.Conclusion. The conclusion of the study describes the advantages of using personalized educational programs developed taking into account the principles of andragogical science in the advanced training system. The conclusions made served as the basis for recommending the introduction of a model of personalized educational programs in the system of additional professional education in order to improve the efficiency of the process of developing professional and personal resources of teaching staff.